2012
DOI: 10.5572/ajae.2012.6.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Artificially Deposited Submicron-sized Aerosol Particles on the Surfaces of Leaves and Needles in Trees

Abstract: To understand the effect of aerosols on the growth and physiological conditions of trees in forests, it is important to know the state of aerosols that are deposited on the surface of the leaves or needles. In this study, we developed methods of visualization of submicron-sized aerosols that were artificially deposited from the gas-phase or liquid phase onto tree leaves or needles in trees. Firstly, we used field-emission scanning electron microscopy (FE-SEM) to observe black carbon (BC) particles that were ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We previously conducted an exposure experiment on leaf and needle surfaces to submicron-sized black carbon (BC) particles to clarify the effects of BC particles on forest trees species [13][14][15]. We also developed a visualization method to determine the deposition and localization of submicron-sized BC particles on tree leaves and needles using field-emission scanning electron microscopy (FE-SEM) [13]. Our findings revealed that (1) carbon-based particles were aggregated on leaves, and (2) carbon-based particles were deposited on the sparse waxy structural area in Cryptomeria japonica [14].…”
Section: Introductionmentioning
confidence: 99%
“…We previously conducted an exposure experiment on leaf and needle surfaces to submicron-sized black carbon (BC) particles to clarify the effects of BC particles on forest trees species [13][14][15]. We also developed a visualization method to determine the deposition and localization of submicron-sized BC particles on tree leaves and needles using field-emission scanning electron microscopy (FE-SEM) [13]. Our findings revealed that (1) carbon-based particles were aggregated on leaves, and (2) carbon-based particles were deposited on the sparse waxy structural area in Cryptomeria japonica [14].…”
Section: Introductionmentioning
confidence: 99%